Valence and lowest Rydberg electronic states of phenol investigated by synchrotron radiation and theoretical methods - Limao-Vieira, P. (2018)
P.L.V. and F.F.S. acknowledge the Portuguese National Funding Agency FCT-MCTES through Grant Nos. UID/FIS/00068/2013 and IF-FCT IF/00380/2014. E.L. acknowledges the Brazilian Agency Conselho Nacional de Desenvolvimento Cientifico e Tecnologico (CNPq) and the Science Without Borders Programme for opportunities to study abroad. D.D. acknowledges support from the CaPPA project (Chemical and Physical Properties of the Atmosphere), funded by the French National Research Agency (ANR) through the PIA (Programme d'Investissement d'Avenir) under Contract No. ANR-10-LABX-005 and by the Regional Council "Nord-Pas de Calais" and the "European Funds for Regional Economic Development" (FEDER). M.A.S. would like to acknowledge the Visiting Research Fellow position at The Open University. This work was performed using HPC resources from GENCI-CINES (Grant No. 2015-088620). The Centre de Ressources Informatiques (CRI) of the Universite of Lille also provided computing time. The authors wish to acknowledge the beam time at the ISA synchrotron at Aarhus University, Denmark. We also acknowledge the financial support provided by the European Community's Seventh Framework Programme (No. FP7/2007-2013) CALIPSO under Grant Agreement No. 312284. M.J.B. acknowledges financial support provided through the Australian Research Council (ARC).